PELAKSANAAN PRAKTIK KERJA LAPANGAN (Studi Kasus pada Kelas XI OTKP SMK Kristen 1 Surakarta) - Avan Sambudi; C. Dyah S. Indrawati; Susantiningrum Susantiningrum (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2020)
The research aimed to find out : (1) Knowing the implementation of Internship Program. (2) Knowing the obstacles of the implementation of Internship Program. (3) Knowing how to overcome the obstacles in the implementation of Internship Program in Christian Vocational High School 1 Surakarta, Automation and Office Management Skills Program.This study is a descriptive qualitative research. The research data is collected from following sources: research participant, event and documentation. The sampling technique used was purposive and snowball sampling. The techniques of data collection are interview, observation, and documentation. To check the validity of the data, the researcher uses source triangulation and method triangulation. Meanwhile the data is analyzed based on the interactive analysis model. The results of the study: (1) The implementation of Internship Program has been well organized and has a positive role. (2) Obstacles that occur such as the distance of partner institutions is too far, less of skills teachers that it cause not all internship supervisors are competent, lack of communication and responsibility of school supervisor. (3) Efforts are made such as election of industry places that are affordable to the student's residence, improving coordination between teachers, performance report to the chief executive.